The Influence of Content Marketing on Brand Image Through Customer Engagement - Nurazizah, Amelia; Sadono, Teguh Priyo; Palupi, Merry Frida Tri (Indonesian Journal Publisher, 2025)
Technological developments have made social media an important component of business marketing strategies, including Netflix, which uses Instagram to increase audience engagement and build a strong brand image. This study aims to determine the effect of content marketing on brand image through customer engagement on the Instagram account @netflixid. The method used is a quantitative approach with Structural Equation Modeling (SEM) analysis. Data collection through online questionnaires to followers of the Instagram account @netflixid. A sample of 100 respondents with the criteria are followers who have interacted with content on the Instagram account @netflixid. The study found that there is a positive and significant influence of content marketing on customer engagement and brand image. In addition, customer engagement has also been shown to act as a mediator in strengthening the influence of content marketing on brand image. These results emphasize the importance of a relevant and interactive content-based marketing strategy in order to create a positive brand image by increasing customer engagement.